2021
DOI: 10.1002/acp.3787
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of calibration of executive function performance in college learners' regulation

Abstract: Summary This study examined learners' calibration of their executive function performance and the contribution of learners' calibration accuracy to their self‐regulated learning. A measure of calibration bias of EF performance is introduced and an evaluation of the utility of the measure is presented. Direct and indirect measures of EF, an assessment of students' metacognitive strategy use, and academic achievement information were obtained from a sample of 189 college learners. Findings revealed that students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Providing education of EF in addition to SRL probably increases the levels of success in students. Furthermore, metacognitive knowledge about SRL and EF leads to more motivation to use the learned strategies correctly (e.g., Veenman, 2011 ; Follmer, 2021 ). Additionally, in the design of (blended) learning environments, educational professionals can build a certain degree of adaptivity when considering different levels of students’ EF, knowing that individual differences are significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing education of EF in addition to SRL probably increases the levels of success in students. Furthermore, metacognitive knowledge about SRL and EF leads to more motivation to use the learned strategies correctly (e.g., Veenman, 2011 ; Follmer, 2021 ). Additionally, in the design of (blended) learning environments, educational professionals can build a certain degree of adaptivity when considering different levels of students’ EF, knowing that individual differences are significant.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue might be that students over-or underestimate themselves and whether there is a discrepancy between their intentional behavior and what they actually demonstrate [as demonstrated for SRL by Broadbent and Poon (2015)]. Students who overstated their performance on EF performance measures also achieved significantly higher scores on self-reports (Follmer, 2021). Rovers et al (2019) showed that students can report -via questionnaires -relatively accurately what their general selfregulatory functioning is, while at a detailed level, they have difficulty pinpointing exact SRL strategies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation